IMPLEMENTATION OF OBSERVE, CRITICIZE, AND FIX IT (OCF) METHOD IN INCREASING TEACHER'S ABILITY TO ARRANGE QUESTIONS - Oyong Risman (Jurnal PAJAR (Pendidikan dan Pengajaran), 2020)
This research is motivated by teacher ability in arranging questions as an exam outline and the low quality of the questions. Through the Observe, Criticize, and Fix it (OCF) method, it is hoped that the teacher's ability will increase in arranging the questions. This study was an action research conducted at SDN 014 Sidodadi Logas Tanah Darat District with the subjects of the research were 7 teachers. Data was collected through observation sheets and analyzed to see the improvement of the ability of teachers after mentoring with the OCF method. The results of the study in the first cycle obtained an average percentage of teacher abilities with 67.1% which enough category while the second cycle got 85.4% which included in good category. Based on the results of the study, it can be concluded that the ability of SDN 014 Sidodadi Logas Tanah Darat teachers in arraging questions for exam outline has increased through the methods of Observe, Criticize, and Fix it (OCF).